The implications of internet-based Chinese language courses on online classes - Nawaz, Khan (Frontiers in Psychology, 2024)
Interactionist and social-cultural perspectives on second language acquisition suggest that interactions between teachers and students offer promising avenues for acquiring Chinese as a second language, which the vast majority of international students consider difficult. Computer-mediated communication is far safer than face-to-face encounters during the present pandemic. Three aims are being investigated here. It is important to first analyze the differences between traditional classroom and online learning by different modes, then analyze the various ways teachers use computer-mediated communication, and finally analyze the challenges and opportunities presented by online Chinese as a second language courses using qualitative research methods. Three teachers and eighty-four students are analyzed statistically in terms of their multimodal interactions, and the quality of their weekly classroom exchanges is assessed through an interpretive analysis of questionnaire data, all in the name of a mixed-methods approach. Particular attention was paid to the challenges of online tutoring for students, the discrepancy between instructor and student understandings, and the use of several teaching strategies with international students. The online classroom environment places unique demands on the quality of student-teacher communication. Different strategies must be used when teaching non-native speakers of Chinese as a second language compared to teaching in a traditional classroom setting.